Design, Synthesis, and Evaluation of Linker-Optimised PSMA-Targeting Radioligands - Fanny Lundmark; Gustav Olanders; Sara Sophie Rinne; Ayman Abouzayed; Anna Orlova; Ulrika Rosenström (MDPI AG, 2022)
Prostate-specific membrane antigen (PSMA) is overexpressed in the majority of prostate cancer cells and is considered to be an important target for the molecular imaging and therapy of prostate cancer. Herein, we present the design, synthesis, and evaluation of 11 PSMA-binding radioligands with modified linker structures, focusing on the relationship between molecular structure and targeting properties. The linker design was based on 2-naphthyl-L-alanine-tranexamic acid, the linker structure of PSMA-617. X-ray crystal-structure analysis of PSMA and structure-based design were used to generate the linker modifications, suggesting that substitution of tranexamic acid could lead to interactions with Phe546, Trp541, and Arg43 within the binding cavity. After synthesis through SPPS, analogues were labelled with indium-111 and evaluated in vitro for their specific binding, affinity, and cellular retention. Selected compounds were further evaluated in vivo in PSMA-expressing tumour-bearing mice. Based on the results, 2-naphthyl-L-alanine appears to be crucial for good targeting properties, whereas tranexamic acid could be replaced by other substituents. [111In]In-BQ7859, consisting of a 2-naphthyl-L-alanine-L-tyrosine linker, demonstrated favourable targeting properties. The substitution of tranexamic acid for L-tyrosine in the linker led to an improved tumour-to-blood ratio, highlighting [111In]In-BQ7859 as a promising PSMA-targeting radioligand.